Modelling the savvy savannah - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
new modelling software Savanna Future Harvest, PMB 238, 2020 Pennsylvania Avenue, NW, Washington, DC 20006-1846, USA Email: info@futureharvest.org Website: http://www.futureharvest.org/